2020
DOI: 10.1002/acn3.51225
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term adherence and response to botulinum toxin in different indications

Abstract: ObjectiveThe objective of the study was the analysis of adherence and self‐perceived treatment response to long‐term botulinum neurotoxin type A (BoNT‐A) treatment in different neurological indications.MethodsIn this retrospective, monocentric, observational study, cross‐sectional and longitudinal data of 1351 patients documenting 20705 injection appointments at the BoNT outpatient clinic of Heinrich Heine University Duesseldorf between 1989 and 2014 were retrospectively analyzed. Patients had been treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The mean duration of spasticity before the first cycle of injections was 14.52 months (median 5). Our results are in line with a recent study published in 2020, in which adherence to BoNT-A therapy revealed that most treatment dropouts occurred within the first 8 years [ 43 ]. In particular, authors found that long-term therapy adherence was better in blepharospasm, hemifacial spasm, and cervical dystonia patients than in spasticity patients.…”
Section: Discussionsupporting
confidence: 93%
“…The mean duration of spasticity before the first cycle of injections was 14.52 months (median 5). Our results are in line with a recent study published in 2020, in which adherence to BoNT-A therapy revealed that most treatment dropouts occurred within the first 8 years [ 43 ]. In particular, authors found that long-term therapy adherence was better in blepharospasm, hemifacial spasm, and cervical dystonia patients than in spasticity patients.…”
Section: Discussionsupporting
confidence: 93%
“…During the manufacturing process of the incoBoNT/A preparation (Xeomin ® , Merz Pharmaceuticals ® , Frankfurt, Germany), not only the clostridial complex proteins but also biologically inactive fragments are removed, and the total clostridial protein content of a vial of 100 U Xeomin ® is reduced to 0.44 ng [32], which is much lower than that of the aboor onaBoNT/A preparation [32]. This low protein content of the incoBoNT/A preparation leads to a low antigenicity of incoBoNT/A in comparison to abo-or onaBoNT/A, which was confirmed in an animal experiment [33] and in a recent cross-sectional study in patients who received long-term treatment exclusively with incoBoNT/A without NAB induction [18,34].…”
Section: Reasons For the Occurrence Of Stf During Bont/a Therapymentioning
confidence: 60%
“…Previous publications have explored adherence to spasticity treatments. [18][19][20][21][22] However, to the best of our knowledge (see Supplemental Table 7 for search terms), this is one of the first publications to assess real-world adherence to botulinum toxin treatment for spasticity 21,22 and the first to assess adherence to onabotulinumtoxinA specifically across multiple etiologies. Variables associated with adherence and non-adherence to onabotulinumtoxinA treatment in the total and stroke logistic regression models from this analysis of ASPIRE are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…21 Lee et al supports this finding, suggesting that "incapability to return to the clinic owning to organizational issues (e.g., transportation, especially for more disabling disorders such as SPAS [spasticity])" may have negatively impacted long-term adherence to botulinum toxin treatment in their study. 22 Alternatively, longer treatment intervals may be consistent with the patient's prescribed treatment regimen.…”
Section: Variables Associated With Adherence and Non-adherence To Onabotulinumtoxina Treatment In The Final Total Model And Final Stroke mentioning
confidence: 99%
See 1 more Smart Citation